2015
DOI: 10.1016/j.tourman.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Visitors' engagement and authenticity: Japanese heritage consumption

Abstract: Understanding the sense of authenticity of heritage attractions is important for tourism management and marketing because presentation, interpretation and verification has a direct bearing on motivations to visit and engage with heritage tourism sites. This paper establishes relationships among the concepts of culturally specific motivation, perception of authenticity, engagement and attendant behavioral consequences based on domestic visitors' experiences at Japanese heritage sites. It further extends Kolar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
267
3
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(300 citation statements)
references
References 78 publications
22
267
3
8
Order By: Relevance
“…Existentially authentic experiences are not simply about visiting sites of socially constructed significance, but participating and experiencing something fulfilling, engaging, and fundamentally dissimilar to the normality of everyday life (Daugstad and Kirchengast, 2013). Reisinger and Steiner (2006) and Kolar and Žabkar (2010) found that both existential and object-based authenticity were related to cultural motivation, while Bryce et al (2015) suggest that cultural motivation positively influences existential authenticity.…”
Section: Host Sincerity and Related Conceptsmentioning
confidence: 97%
See 2 more Smart Citations
“…Existentially authentic experiences are not simply about visiting sites of socially constructed significance, but participating and experiencing something fulfilling, engaging, and fundamentally dissimilar to the normality of everyday life (Daugstad and Kirchengast, 2013). Reisinger and Steiner (2006) and Kolar and Žabkar (2010) found that both existential and object-based authenticity were related to cultural motivation, while Bryce et al (2015) suggest that cultural motivation positively influences existential authenticity.…”
Section: Host Sincerity and Related Conceptsmentioning
confidence: 97%
“…This involves extending the CBA (cf. Bryce et al, 2015;Zhou et al, 2013) by incorporating a host sincerity scale into the model. Thus, this updated model explores relationships surrounding cultural motivation, authenticity, host sincerity, and memorable tourism experiences.…”
Section: Host Sincerity and Related Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the findings above imply, such positive changes appear to have occurred in Kii WHS. As noted previously, WHS status may function as an indicator of objective authenticity for tourists (Poria et al, 2013;Smith, 2002) and create a marketable brand for the destination (Bryce et al, 2015). WHS status seems to have worked on Kii as a marker of authenticity and quality for foreign tourists and may be a reason why Kii has seen an evident increase in the number of overseas tourists since its WHS inscription.…”
Section: Tourism and Global Recognitionmentioning
confidence: 82%
“…WHS 5 status may also be an ostensible marker of authenticity and a measure of quality (Bianchi, 2002;Poria, Reichel & Cohen, 2013;Smith, 2002). In short, acquiring WHS status can mean external validation and 'branding' by an international authenticating organisation such as UNESCO (Bryce, Curran, O'Gorman, & Taheri, 2015).…”
Section: Destination Communities World Heritage Management and Tourismmentioning
confidence: 99%